2011
DOI: 10.1103/physrevb.83.155403
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the range of influence of point defects on Cu (110) surface states

Abstract: By utilizing reflection anisotropy spectroscopy (RAS) and scanning tunneling microscopy (STM) measurements of the ion-bombarded Cu (110) surface at low temperatures, we have developed a simple methodology for estimating the effective surface area over which irradiation-induced defects perturb surface states, leading to a reduction in the intensity of the 2.1 eV RAS peak of this surface. Each composite defect decorating an ion-impact site quenches the RAS signal in proportion to an area equivalent to approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The larger effective defect radius for a single ion impact revealed in other studies [27] [34] [35] would cause the simulated curves to decrease in intensity for lower sputter doses, and would more quickly approach zero intensity, but these effects do not change our results for the range of sputtering and necessary patch size presented. To verify this, the simulation was also performed assuming 0-2 atom removal per ion collision, effectively decreasing the mean ion damage area in the simulation with little change to the results displayed.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The larger effective defect radius for a single ion impact revealed in other studies [27] [34] [35] would cause the simulated curves to decrease in intensity for lower sputter doses, and would more quickly approach zero intensity, but these effects do not change our results for the range of sputtering and necessary patch size presented. To verify this, the simulation was also performed assuming 0-2 atom removal per ion collision, effectively decreasing the mean ion damage area in the simulation with little change to the results displayed.…”
Section: Discussionmentioning
confidence: 59%
“…This is supported by the conclusions of Vasylyev and coworkers in their study of low-energy Ar ion bombardment on low index nickel surfaces [34], where it was suggested that low-dose sputtering on this system likely produces vacancy point defects and adatoms with mean damage area per ion collision of about 5 unit cells. We note, however, that other authors have reported various higher estimates for the yield and damaged area per ion impact [27] [34] [35].…”
Section: Simulationsmentioning
confidence: 59%
See 1 more Smart Citation
“…On the other hand, subsurface defects influence the bulk electronic structure in the near-surface region, with a pronounced effect on the corresponding optical anisotropy. In fact, the sensitivity of RDS to thermally and ion-induced defects on noble metal surfaces has been recognized by several authors in the past 10 15 . In particular, a sensitive dependence of the surface-states-related RD signal on the surface defect concentration and distribution has been elucidated 15 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Reflectance difference (RD/RA) spectroscopy 1–12 is a powerful tool for the optical characterizations of surfaces and interfaces. Among the applications of RD, we can mention the characterization of novel surface processes 13, surface electric fields 14–21, defects, and strain 22–28. The development of the RD spectroscopy as an optical probe for the characterization of surfaces and interfaces has suggested that an extension of the RD spectroscopy to a microscopic scale Micro reflectance difference (µ‐RD) could further increase the potential of the technique.…”
Section: Introductionmentioning
confidence: 99%